162 Digestibility of energy and nutrients and concentration of metabolizable energy in soybean expellers and soybean meal fed to growing pigs. (30th November 2020) - Rodriguez, Diego A; Lee, Su A; Stein, Hans H
Abstract: Two experiments were conducted to test the hypothesis that energy and nutrient digestibility and concentrations of DE and ME are greater in soybean expellers than in soybean meal (SBM) fed to growing pigs. In Exp. 1, two diets based on soybean expellers or SBM as the sole source of AA and an N-free diet were formulated. Nine cannulated barrows (BW: 55.98 ± 13.75 kg) were allotted to a triplicated 3 × 3 Latin square design with 3 diets and 3 periods. Ileal digesta were collected on d 6 and 7 of each 7-d period. The statistical model included ingredient as fixed effect and square, period, and animal as random effects. Results indicated that the standardized ileal digestibility (SID) of most AA were greater (P < 0.05) or tended to be greater (P < 0.10) in soybean expellers compared with SBM (Table 1). In Exp. 2, a corn-based diet and 2 diets based on corn and each of the 2 soybean products were formulated. Twenty-four barrows (BW: 44.88 ± 2.17 kg) were allotted to 1 of the 3 diets with 8 pigs per diet. Urine and fecal samples were collected for 4 d after 5 d of adaptation. The statistical model included diet or ingredient as fixed effect and replicate as random effect. Results indicated that the apparent total tract digestibility (ATTD) of GE was not different among pigs fed the 3 diets. Concentrations of DE and ME in soybean expellers were greater (P < 0.05) compared with SBM, but the ATTD of total dietary fiber was not different between the 2 soybean products. In conclusion, values for SID of most AA and the DE and ME in soybean expellers were greater than in SBM.